2021
DOI: 10.3389/fnins.2021.647168
|View full text |Cite
|
Sign up to set email alerts
|

Nigral Iron Deposition Is Associated With Levodopa-Induced Dyskinesia in Parkinson’s Disease

Abstract: ObjectiveTo investigate iron deposition in the substantia nigra (SN) of Parkinson’s disease (PD) patients associated with levodopa-induced dyskinesia (LID).MethodsSeventeen PD patients with LID, 17 PD patients without LID, and 16 healthy controls were recruited for this study. The mean QSM values of the whole, left, and right SN were compared among the three groups. A multivariate logistic regression model was constructed to determine the factors associated with increased risk of LID. The receiver operating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Our retrospective study indicated that early and regular treatment with levodopa prevented the loss of DNH and alleviated the symptoms of PD. A recent study suggested that the nigral iron deposition was associated with levodopa-induced dyskinesia ( Song et al, 2021 ). However, in our study, decreased loss of DNH was observed in one patient with more severe dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…Our retrospective study indicated that early and regular treatment with levodopa prevented the loss of DNH and alleviated the symptoms of PD. A recent study suggested that the nigral iron deposition was associated with levodopa-induced dyskinesia ( Song et al, 2021 ). However, in our study, decreased loss of DNH was observed in one patient with more severe dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…35 Nigral cell degeneration leads to the functional alterations of basal ganglia, which are related to motor dysfunction in patients with PD. 11,36 On the other side, some studies suggested that iron accumulation might also result from dopaminergic cell degeneration. 37,38 NM is a pigment and is particularly abundant in dopamine neurons of the SN and in the noradrenergic neurons of locus coeruleus.…”
Section: Discussionmentioning
confidence: 99%
“…A study using quantitative susceptibility mapping (QSM) imaging showed that the QSM values of SN in PD-LID were higher than in PD without LID (PD-nLID), suggesting that dyskinesia is related to excessive iron deposition in SN. 11 However, current studies in LID mainly focus on the entire SN; the dopaminergic changes in the subregions of SN have not been investigated. The substantia nigra pars compacta (SNpc) is composed of closely packed dopaminergic neurons, 12 which may contribute to the abnormal dopaminergic responses that result in LID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the published studies did not always identify the same regions of interest and did not consider the medications that the patients were taking at the time the FDG-PET or QSM–MRI brain imaging studies were performed. For example, subjects with levodopa-induced dyskinesia have more iron in the substantia nigra than those without it [ 83 ]. It is also apparent that the results would be more accurate if studies were identified where FDG-PET and QSM–MRI were both conducted on the same patients or on age- and sex-matched pairs.…”
Section: Discussionmentioning
confidence: 99%